2007
DOI: 10.4049/jimmunol.179.3.1740
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Involvement of Mast Cells and T Cells in Allergic Mucosal Inflammation: Critical Role of the CC Chemokine Ligand 1:CCR8 Axis

Abstract: CCL1 is the predominant chemokine secreted from IgE-activated human and mouse mast cells in vitro, colocalizes to mast cells in lung biopsies, and is elevated in asthmatic airways. CCR8, the receptor for CCL1, is expressed by ∼70% of CD4+ T lymphocytes recruited to the asthmatic airways, and the number of CCR8-expressing cells is increased 3-fold in the airways of asthmatic subjects compared with normal volunteers. In vivo, CCL1 expression in the lung is reduced in mast cell-deficient mice after aeroallergen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 52 publications
1
62
0
1
Order By: Relevance
“…In addition, the number of CD4+ lymphocytes or mast cells did not contribute independently to improvement of BHR. Thus, in contrast to asthma, our findings do not suggest a large contribution of CD4+ lymphocytes or mast cells to the severity of BHR in COPD, but rather highlight the contribution of sputum neutrophils, lymphocytes and macrophages [32,33].…”
Section: Discussionmentioning
confidence: 65%
“…In addition, the number of CD4+ lymphocytes or mast cells did not contribute independently to improvement of BHR. Thus, in contrast to asthma, our findings do not suggest a large contribution of CD4+ lymphocytes or mast cells to the severity of BHR in COPD, but rather highlight the contribution of sputum neutrophils, lymphocytes and macrophages [32,33].…”
Section: Discussionmentioning
confidence: 65%
“…Our results further support a role for these other cell types contributing to the total levels of Th2 cytokines in the lung, yet not to the level attainable when CD4 + T cells also contribute. Mast cells are an abundant source of CCL1 following FcεRI-mediated activation and are critically important in the chemotactic recruitment of CCR8-expressing CD4 + T cells (25,38), a relationship central in the development of asthmatic mucosal inflammation in the lung (7). We have detected a deficiency of CCL1 in the lungs of asthmatic mice with Egr2-deficient mast cells (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…Mast cells can direct the migration of CD4 + CD25 + T regulatory cells through the CCL1-CCR8 axis (7,25). To investigate the role of Egr2-dependent mast cell CCL1 in T cell migration, an in vitro Transwell migration assay was conducted.…”
Section: Egr2-dependent Mast Cell Ccl1 Production Drives Cd4 + T Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemokines are a class of small molecules, which promote leukocyte migration toward themselves [12]. CCL-1 is among the first discovered CC class of chemokines, which are mainly secreted by activated T cells, mast cells and macrophages [13][14][15][16][17]. Recently, it has been shown that autocrine CCL-1 produced from leukocellular lymphoma and adult cell leukemia has an anti-apoptotic effect [18].…”
Section: Discussionmentioning
confidence: 99%